2016
DOI: 10.1161/hypertensionaha.115.06689
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Stimulation of Cardiac Hypertrophy and Functional Decompensation in Osteoprotegerin-Deficient Mice

Abstract: SummaryOsteoprotegerin plays a critical role in angiotensin II-induced cardiac remodeling, and lack of this gene leads to dilate left ventricular chamber, resulting in functional left ventricular decompensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Cardiac hypertrophy and pulmonary oedema are serious complications that often occur in the final stages of HF (Delafontaine & Akao, 2006;von Haehling, Ebner, Dos Santos, Springer, & Anker, 2017). To observe the progression of Ang IIinduced HF, rat heart/body weight ratios (Figure 2g) and lung/body weight ratios (Figure 2h) and gastrocnemius muscle weight/body weight ratio (Figure 2i) were determined at the end of the experiment, as in earlier studies (Tsuruda et al, 2016;Wang, Chen, et al, 2018;Wang, Fernandez-Sanz, & Sheu, 2018). Our data showed that Ang II-induced marked rat body weight loss (cachexia) and pulmonary oedema, which was not observed in the Ang II + SIM group.…”
Section: Simvastatin Improves Cardiac Function In Ang Ii-induced Hfmentioning
confidence: 91%
“…Cardiac hypertrophy and pulmonary oedema are serious complications that often occur in the final stages of HF (Delafontaine & Akao, 2006;von Haehling, Ebner, Dos Santos, Springer, & Anker, 2017). To observe the progression of Ang IIinduced HF, rat heart/body weight ratios (Figure 2g) and lung/body weight ratios (Figure 2h) and gastrocnemius muscle weight/body weight ratio (Figure 2i) were determined at the end of the experiment, as in earlier studies (Tsuruda et al, 2016;Wang, Chen, et al, 2018;Wang, Fernandez-Sanz, & Sheu, 2018). Our data showed that Ang II-induced marked rat body weight loss (cachexia) and pulmonary oedema, which was not observed in the Ang II + SIM group.…”
Section: Simvastatin Improves Cardiac Function In Ang Ii-induced Hfmentioning
confidence: 91%
“…Interestingly, we also found that patients who were on higher doses of renin-angiotensin-system (RAS) blockers had lower OPG levels. This is indirectly supported by Tsuruda et al who demonstrated that OPG levels increase in response to cardiac damage during angiotensin II-induced hypertrophy in mice [45]. Therefore, the question is raised whether serial assessment of circulating OPG may be used to identify patients who respond poorly to RAS inhibition.…”
Section: Discussionmentioning
confidence: 93%
“…ANG II-induced upregulation of osteoprotegerin by cardiac cells, including infiltrating macrophages, was found to protect against the development of eccentric hypertrophy and dilated cardiomyopathy by enhancing collagen synthesis and inhibiting cardiac myocyte apoptosis. Osteoprotegerin is a secretory glycoprotein belonging to the TNF receptor superfamily that generally acts as a decoy receptor for RANKL, but that was not so in this case (1070). Although not well studied, the engagement of adaptive immunity by ANG II may also impact on cardiac hypertrophy and overall structural remodeling of the heart.…”
Section: Ang II In Cardiac Hypertrophymentioning
confidence: 88%